Amantadine for treatment of fatigue in Guillain-Barré syndrome: a randomised, double blind, placebo controlled, crossover trial. Issue 1 (16th December 2005) - Garssen, M P J; Schmitz, P I M; Merkies, I S J; Jacobs, B C; van der Meché, F G A; van Doorn, P A
Abstract : Objective: Fatigue is a major complaint in patients with immune mediated polyneuropathies. Despite apparently good physical recovery after Guillain-Barré syndrome (GBS), many patients remain restricted in daily and social activities, and have a decreased quality of life. In this trial, the effect of amantadine on severe fatigue related to GBS was studied. Methods: During the pre-treatment phase, all patients were monitored for 2 weeks. Only patients with severe fatigue, defined as a mean fatigue score of ⩾5.0 on the Fatigue Severity Scale (FSS), were randomised for this double blind, placebo controlled, crossover study. Primary outcome measure was improvement of at least 1 point on the FSS. Secondary outcome measures were impact of fatigue, anxiety and depression, handicap, and quality of life. Results: In total, 80 patients with GBS were randomised, of whom 74 were included for analysis. Fatigue appeared to be reduced already during the pre-treatment phase (p = 0.05), probably due to increased attention provided to the patients. No significant differences in any of the primary and secondary outcome measures were found. Conclusions: Amantadine was not superior to placebo. Because fatigue remains a serious complaint, other studies evaluating new treatment options are strongly recommended.